Rapid Solidification Processing and Bulk Metallic Glass Casting - S. N., Aqida; L. H., Shah; Naher, S.; Brabazon, D. (Elsevier Ltd, 2014)
The early development of metallic glasses was achieved through the rapid cooling of micrometer-thick thin ribbons via planar flow casting. These early developments were made with alloy compositions that could not be cast into thicker sections while maintaining their amorphous nature. This limitation was due to the relatively slower cooling rates resulting from the larger volume and associated energy contained within these larger volume sections. The problem of casting larger sections with amorphous structures was overcome primarily by the discovery of new alloy compositions that do not necessitate as high a cooling rate, as well as by designing processes that allow for more rapid cooling for larger volumes. Bulk metallic glass (BMG) processing was established with modified centrifugal casting, die casting, and splat casting techniques that incorporate high-speed injection and suction mechanisms, as well as high thermal conductivity copper molds. Although many casting techniques have been reported, the main goal has been to improve the glass-forming ability (GFA) and thus achieve larger section thicknesses that remain amorphous within the BMG alloy component. Most investigations on the development of BMG alloys have examined the effects of thermal field and alloy composition on the properties of BMG alloys. In particular, the effects of multicomponent BMG alloy systems containing rare earth, transition metals, and metalloids elements have been investigated.